The Effectiveness of Applying E-Book in Teaching Indonesian to Speakers of Other Languages (TISOL) in Supporting Foreign Students’ Self-Learning in Indonesia - Hastuti, Sri; Saddhono, Kundharu; Marmoah, Sri; Rahmawati, Endang; Uswatun Hasanah, Dian; Rosita, Farida Yufarlina; Inderasari, Elen; Arifah, Irma; Puji Rahmawati, Fitri; Widianti, Nurhannah; Jazeri, Mohamad; Maulida, Siti Zumrotul; et al. (International Journal of Engineering and Technology, 2018)
The study aims to test the effectiveness of TISOL E-book in supporting foreign students’ self-learning in Indonesian higher education in Java Island. It employed experimental method. The result of effectiveness test concludes that foreign students’ language proficiency with using TISOL e-book is better than using conventional textbook. The result of applying TISOL e-book shows that Indonesian language proficiency is measured with three component: language proficiency, writing scientific paper and scientific presentation. The result shows that there are differences of pretest-posttest among experiment and control groups in higher education implementing TISOL in Indonesia. F-test results as much as 9,775 with statistical significance of 0.000 < 0.05. Therefore, Ho is rejected and data among groups have the significant differences.
Keywords: effectiveness; e-book; TISOL; self-learning; foreign students